Mid-Pleistocene aridity and landscape shifts promoted Palearctic hominin dispersals - Jinbo Zan; Julien Louys; Robin Dennell; Michael Petraglia; Wenxiao Ning; Xiaomin Fang; Weilin Zhang; Zhe Hu (Nature Communications)
Abstract Population expansions and contractions out of and into Africa since the early Pleistocene have influenced the course of human evolution. While local- and regional-scale investigations have provided insights into the drivers of Eurasian hominin dispersals, a continental-scale and integrated study of hominin-environmental interactions across Palearctic Eurasia has been lacking. Here, we report high-resolution (up to ∼5-10 kyr sample interval) carbon isotope time series of loess deposits in Central Asia and northwest China, a region dominated by westerly winds, providing unique paleoecological and paleoclimatic records for over ~3.6 Ma. These data, combined with further syntheses of Pleistocene paleontological and archaeological records and spatio-temporal distributions of Eurasian eolian deposits and river terraces, demonstrate a pronounced transformation of landscapes around the Mid-Pleistocene Climate Transition. Increased climate amplitude and aridity fluctuations over this period led to the widespread formation of more open habitats, river terraces, and desert-loess landscapes, pushing hominins to range more widely and find solutions to increasingly challenging environments. Mid-Pleistocene climatic and ecological transitions, and the formation of modern desert and loess landscapes and river networks, emerge as critical events during the dispersal of early hominins in Palearctic Eurasia.